Device occlusion of pseudoaneurysm of ascending aorta - Mridul Agarwal; Mili Ray; M Pallavi; Supratim Sen; Debosree Ganguly; Pankaj Joshi; Sanjay Tanti; Amitabh Chattopadhyay; Biswajit Bandyopadhyay (Annals of Pediatric Cardiology, 2011)
Pseudoaneurysm of ascending aorta is an infrequent but well-recognized and potentially fatal complication after cardiac surgeries. The complication can develop early, delayed or late, and the presentation is also varied. We are presenting here two cases of pseudoaneurysm of ascending aorta following cardiac surgery that were successfully managed by the transcatheter method. The first one occurred following coronary artery bypass surgery and the second one occurred following double-valve replacement surgery. The aortic openings of these aneurysms were occluded with 12 mm and 10 mm atrial septal occluders, respectively, with a good outcome. An immediate postprocedure angiogram showed no residual flow into the sac. Six months of follow-up of both cases also showed excellent results.